Apoptosis and BRCA1 gene mutations in women with breast cancer from the Lodz region of Poland - Romanowicz-Makowska, Hanna; Smolarz, Beata; Zadrożny, Marek; Stetkiewicz, Tomasz; Pertyński, Tomasz; Kulig, Andrzej (Menopause Review/Przegląd Menopauzalny, 2005)
Aim: The breast cancer susceptibility gene BRCA1 encodes a large multi-functional protein which is implicated as a caretaker of the genome, through its role in regulation of DNA damage response pathways, including apoptosis. Apoptotic cell death plays important role in the pathogenesis and disease progression of cancer as well as in the response to treatment. The objectives of this study were to determine the frequency of BRCA1 germ-line mutations and apoptosis in patients with breast cancer. Materials and methods: 40 breast cancer women provided blood for genetic analysis. Blood samples age matched healthy individuals (n=42) served as control. The BRCA1 mutations were determined by PCR-RFLP methods. The apoptotic peripheral blood cells were detected by agarose gel electrophoresis. Results: The apoptotic cells were identified in 30% (12/40) of the patients. There were no significant differences in apoptosis frequencies between patients and controls (P > 0.05). one Ex20insC mutations of BRCA1 gene were identified in breast cancer patients. Conclusion: The presence of apoptotic peripheral blood cells in patients suggests a potential role of apoptosis in risk breast cancer appearance. The lack of detectable BRCA1 germ-line mutations in most cases suggests that there are probably additional, as yet unidentified genes predisposing to this disease.